2016
DOI: 10.1134/s160767291605001x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of proteins of the vesicle cycle in the striatum and motor cortex under functional failure of nigrostriatal system

Abstract: Degeneration of dopaminergic neurons in the substantia nigra and the decrease in the dopamine level in the striatum lead to dysfunctions of motor behavior. This is accompanied by dysregulation of neuro-transmission in glutamatergic neurons of the motor cortex and GABA-ergic neurons of the striatum. It is shown that dysregulation of the gene expression of vesicle cycle proteins in neurons of the motor cortex occurs at an early (presymptomatic) stage of degeneration of the nigrostriatal system, and in more sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Interestingly, SNAP-25 was increased in CSF of PD patients and different single-nucleotide polymorphisms (SNPs) have been associated with the pathogenesis of PD [ 61 ]. Furthermore, a study conducted in mice has shown that in a model of the preclinical stage of PD an increase in the expression of syntaxin-1a was detected whereas in the model of the clinical stage of PD, a reduction in the expression of this gene, and others involved in exocytosis and endocytosis, occurred [ 41 ].…”
Section: Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, SNAP-25 was increased in CSF of PD patients and different single-nucleotide polymorphisms (SNPs) have been associated with the pathogenesis of PD [ 61 ]. Furthermore, a study conducted in mice has shown that in a model of the preclinical stage of PD an increase in the expression of syntaxin-1a was detected whereas in the model of the clinical stage of PD, a reduction in the expression of this gene, and others involved in exocytosis and endocytosis, occurred [ 41 ].…”
Section: Pdmentioning
confidence: 99%
“…Molecules affected by SNARE proteins and their functions in neurodegenerative diseases are reported in Table 2 . A role of SNARE proteins in the pathophysiology of AD, PD and ALS has been discovered [ 30 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%